2014
DOI: 10.1111/iju.12560
|View full text |Cite
|
Sign up to set email alerts
|

Robot‐assisted laparoscopic high‐intensity focused ultrasound for focal therapy of prostate: Novel approach

Abstract: Focal therapy for prostate cancer is an experimental approach, and the best candidate for the focal targeted therapy continues to evolve along with the development of therapeutic modalities. HIFU delivers ultrasonic energy to a focal area of tissue with resultant local heat and complete coagulative necrosis. [1][2][3][4] Transrectal HIFU has been proven to be capable of providing long-term local control of prostate cancer.5-7 A novel FDA (510k)-cleared laparoscopic HIFU probe for soft tissue ablation has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 7 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…HIFU has been used for ablating several different types of cancer, including pancreas, bone, breast, liver, soft tissue and others. Within urological oncology, transrectal HIFU ablation of prostate cancer has been used extensively in Europe; in addition, a few studies have shown proof‐of‐concept for lap‐HIFU ablation of small renal masses . Herein, we explore the concept, and determine the technical feasibility of targeted ablation of the intact bladder wall and tumor using a lap‐HIFU approach in the human cadaver and live large animal model.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…HIFU has been used for ablating several different types of cancer, including pancreas, bone, breast, liver, soft tissue and others. Within urological oncology, transrectal HIFU ablation of prostate cancer has been used extensively in Europe; in addition, a few studies have shown proof‐of‐concept for lap‐HIFU ablation of small renal masses . Herein, we explore the concept, and determine the technical feasibility of targeted ablation of the intact bladder wall and tumor using a lap‐HIFU approach in the human cadaver and live large animal model.…”
Section: Discussionmentioning
confidence: 99%
“…However, the laparoscopic HIFU probe destroys all the tissue from its point of contact on the tissue outward, therefore it does not spare any intervening tissue. When compared with the traditional transrectal HIFU probe, the lap‐HIFU probe is thinner, longer, contains a larger ablation zone, delivers energy continuously and causes complete tissue necrosis . Finally, the laparoscopic probe is more powerful and efficient than the transrectal probe, thus enabling treatment of larger tissue volumes in a shorter amount of time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations